Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1007/s11187-006-9018-x
|View full text |Cite
|
Sign up to set email alerts
|

Growth Aspirations and Cultural Support for Entrepreneurship: A Comparison of Post-Socialist Countries

Abstract: Based on GEM data this paper explores whether significantly different growth aspirations of early stage entrepreneurs in Slovenia, compared to those in Hungary and Croatia, are also accompanied by significantly different opportunity recognition, cultural support for entrepreneurship and self-efficacy. Our results suggest that a higher degree of alertness to unexploited perceived opportunities, and cultural support for entrepreneurial motivation may be the cause of higher growth aspirations of Slovenian early s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(72 citation statements)
references
References 35 publications
3
65
0
4
Order By: Relevance
“…According to our results, during the crisis the influence of perceived opportunities on social entrepreneurship increased 37 % compared with the period before the crisis. Similar to previous results (Lehner & Kaniskas, 2012;Roy et al, 2014;Tominc & Rebernik, 2007), perceived opportunities are found to be related to entrepreneurial intentions and are a key driver in the decision to start a new business.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…According to our results, during the crisis the influence of perceived opportunities on social entrepreneurship increased 37 % compared with the period before the crisis. Similar to previous results (Lehner & Kaniskas, 2012;Roy et al, 2014;Tominc & Rebernik, 2007), perceived opportunities are found to be related to entrepreneurial intentions and are a key driver in the decision to start a new business.…”
Section: Resultssupporting
confidence: 87%
“…Accordingly, patterns can be negative (not-feasible opportunity) or positive (suggesting that this opportunity can be a business opportunity). Hence, it is important to note that these perceived opportunities are related to entrepreneurial intentions (Reed, Storrud-Barnes, & Jessup, 2012), and are vital in the decision to start a new entrepreneurial project, especially during economic downturns (Tominc & Rebernik, 2007). Therefore, the following hypothesis is proposed:…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…At the extreme, several scholars claim to have measured ESE by simply asking subjects to respond to one or two questions regarding their confidence in starting a new venture. As an illustration, in a recent study by Tominc and Rebernik (2007), respondents were asked to provide a yes or no response to the question, "Do you have the knowledge, skills, and experience required to start a new business? "…”
Section: Unidimensional Versus Multi-dimensional Measures Of Esementioning
confidence: 99%
“…One of the challenges related to this research is that the issue is discussed with many names. For example, growth ambitions (Gundry & Welsch, 2001), growth willingness (Davidsson, 1989), intended growth and growth intentions (Cassar, 2006), growth preferences (Cassar, 2007), attitude toward growth (Cliff, 1998;Wiklund, Davidsson, & Delmar, 2003), and growth aspirations (Kolvereid, 1992;Tominc & Rebernik, 2007) are all terms that are used in studies that generally aim to understand why and how entrepreneurs seek (or do not seek) high growth. Although these concepts have varying meanings for growth, many of those regard growth as increase in employment.…”
Section: Growth Ambitionsmentioning
confidence: 99%